PENGARUH DIGITAL MARKETING, POTONGAN HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGGUNA SHOPEE - Dewantara, Rezza Ananda; Hayuningtias, Kristina Anindita (Jurnal Manajemen dan Profesional, 2025)
The purpose of this study is to analyze the influence of digital marketing, discounts, and product quality on purchasing decisions. This study focuses on consumers who actively use Shopee to shop for various product categories within a certain period. The population in this study is all Shopee users. This study used a purposive sampling technique. The data analysis technique used is multiple linear regression analysis. The results of the study can be concluded that digital marketing and discounts have a positive and significant influence on purchasing decisions, while product quality has no effect on purchasing decisions. These results explain that the more effective the digital marketing strategy and the more attractive the discounts offered, the more likely consumers are to make a purchase. Conversely, product quality does not show a significant influence on purchasing decisions, indicating that consumer purchasing decisions in the context of this study are more influenced by promotional aspects and price than product quality itself.